Cultivo de tejidos - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
During 1981, the efforts to use meristem-culture methods have continued, together with thermotherapy for recovering healthy clones. Frog skin disease was eradicated up to 100 percent in different cassava clones during various propagation cycles through the culture of small meristem tips. A routine "cleaning-up" program consists of: (1) disinfestation of stakes containing dormant buds and treatment with thermotherapy; (2) cutting and disinfestation of shoot terminal buds; (3) isolation of meristem tips (0.5-0.6 mm) under sterile conditions and planting in culture medium; (4) transfer of meristem tips and nodes grown from the meristem to a rooting medium; (5) hardening of rooted plantlets prior to potting; (6) transplant to the field and to the greenhouse; (7) evaluation of the presence of frog skin disease after 3 mo. of growth; and (8) selection of symptom-free plants, grown again for 3 mo., and reevaluated. A germplasm bank in vitro is a long-term goal to conserve material and to isolate microorganisms. The main steps and procedures followed in the international exchange of clonal materials are described. During 1981, work was initiated aimed atdeveloping anther-culture methods for cassava and to observe microsporogenesis stages in relation to the size of the floral bud. (CIAT)